The transparency of the banking industry and the efficiency of information-based bank runs - Yehning Chen; Iftekhar Hasan (Bank of Finland, 2005)
In this paper, we investigate the relationship between the transparency of banks and the fragility of the banking system.We show that information-based bank runs may be inefficient because the deposit contract designed to provide liquidity induces depositors to have excessive incentives to withdraw.An improvement in transparency of a bank may reduce depositor welfare through increasing the chance of an inefficient contagious bank run on other banks.A deposit insurance system in which some depositors are fully insured and the others are partially insured can ameliorate this inefficiency.Under such a system, bank runs can serve as an efficient mechanism for disciplining banks.We also consider bank managers' control over the timing of information disclosure, and find that they may lack the incentive to reveal information about their banks.
URN:NBN:fi:bof-20140807644
Keywords: G21; G28; 330; bank run; contagion; transparency; market discipline; deposit insurance